Seasonal variation in nutritional content of the kelp Ecklonia maxima on the west and south west coasts of South Africa, with reference to its use as abalone feed - Smith, Melanie Jayne (Department of Oceanography, 2014)
Includes bibliographical references (leaves 62-71).